A geoarchaeological methodology for sourcing chert artefacts in the Mediterranean region: A case study from Neolithic Skorba on Malta. Issue 6 (13th July 2020) - Chatzimpaloglou, Petros
Abstract: This article introduces a robust scientific methodological approach that has been effective on accurately sourcing prehistoric chert artefacts. The research focuses on the lithic assemblage of Skorba, a late Neolithic site of Malta, and local chert rock sources. This assemblage is mainly consisting of chert tools and artefacts, but the origin of the raw materials remains inconclusive. Although chert outcrops are reported on Malta, they have yet to be investigated and their petrological characteristics are unknown. Moreover, it was always assumed that nonlocal chert material has been only imported from Sicily. This, however, remains at a theoretical level and elaborate provenance research is necessary to test it. This archaeological background serves an excellent opportunity to employ an interdisciplinary methodology and address uncertainties that conventional archaeological practices seem unable to provide clear answers. This methodology includes geological techniques that focus on petrological and geochemical characteristics of chert formations. The collected results provide the necessary scientific evidence to connect some artefacts with their actual sources and provided useful information about the possible origin of others. This paper further aims to demonstrate the great prospects of this suite of techniques and its suitability for similar provenance studies of chert material worldwide.